ANALISIS UNSUR INTRINSIK NOVEL “SI CAMAR JONATHAN LIVINGSTON” KARYA RICHARD BACH - Yeli Janianti Suhendi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Literary writing is far more interesting when combined with intrinsic elements that can attract readers from all over world, be it children, youth, adults, and parents. The analysis of the novel is intended to describe an intrinsic element contained in Richard Bach’s attributed to “Si Camar Jonathan Livingston”. The method used in this study is a qualitative descriptive method. The study suggests that Richard Bach’s “Si Camar Jonathan Livingston” novel has the theme of freedom to live, the characters in the novel are so interesting to read, using furrows, settings, times and settings. The viewpoint used was the third omniscient and there was a mandate always to try and unyielding to achieve what lay in the face of obstacles.